Analysis of Capital Structure and Revolution of pharmaceutical industry in Pakistan over the Decade (Global Journal of Management and Business Research, 2012)
This study is conducted to analyze the pharmaceutical sector and its affiliated factors that affects it performance / profitability. We have chosen these factors i.e. Paid up capital, financial charges, stock dividend, sales (mill), cash dividend, taxation, PBT, tax, no of shares etc. from 2001 to 2010. For our analysis we use regression analysis and generate our results. Profit of the pharmaceutical industry depends upon the sales, investment, cash etc. Also, Pakistan pharmaceutical industry do not have so much these above particulars as compare to the multinational pharmaceutical companies, due to which the growth factor reduces a lot. So, overcome these multinational and make a good share in the market the policies of government should be according to the favor of this industry and the industry should also take prominent steps for its growth.
Keywords: Pharma; Material; Demographic and paid up capital